A machine learning based approach to factors predicting correlation between Hb1Ac and diabetes in patients of malnourished communities - Mishra, Sweta; Litoriya, Ratnesh (Journal of Neonatal Surgery, 2025)
Type 1 diabetes mellitus (T1DM) is associated with acute complications such as diabetic ketoacidosis (DKA) and long-term glycemic dysregulation. This study aimed to develop and validate machine learning models to predict DKA episodes and glycemic control, defined as HbA1c >7%, using a large multi-center, bi-national database from the Diabetes Data Network (DDN). Nine machine learning algorithms, including Deep Learning (DL), Support Vector Machine (SVM), Random Forest (RF), and Logistic Regression (LR), were trained and validated on clinical and demographic features collected longitudinally from 10,868 individuals aged 2–21 years between January 2012 and May 2022. The DL model demonstrated the highest predictive performance for DKA, achieving an area under the curve (AUC) of 0.887, while SVM was most effective in predicting HbA1c >7% with an AUC of 0.884. Key predictors for DKA included age at diagnosis, diabetes duration, prior DKA events, BMI z-score, HbA1c, CGM use, insulin regimen, and center. For HbA1c prediction, baseline HbA1c and BMI emerged as dominant features. The results suggest that integrating machine learning models into clinical care could enable early identification of high-risk individuals, facilitating timely interventions and potentially reducing hospitalization rates and healthcare costs associated with T1DM complications. These models underscore the importance of personalized management strategies and highlight the feasibility of real-world application in diabetes clinics.